Synthesis and crystal structure of [Sr(urea)(NO3)2]n - Bektursinova, Aysanem; Djumanazarova, Zulfiya; Uzakbergenova, Zamira; Ashurov, Jamshid; Khan, Akram A.; Kadirova, Shakhnoza; Torambetov, Batirbay (Acta crystallographica Section E, Crystallographic communications, 2025)
The crystal structure of poly[di-μ<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2-nitrato-μ<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2-urea-strontium(II)], [Sr(NO<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">3)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2(CH<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">4N<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2O)] <span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">n , was determined using single-crystal X-ray diffraction. Crystallizing in the ortho-rhom-bic space group <i style="box-sizing: inherit; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px;">Aba2, the asymmetric unit consists of an Sr<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">II cation, two nitrate anions, and two half urea mol-ecules. The Sr<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">II cation adopts a distorted deca-hedral geometry coordinated by ten oxygen atoms, with Sr-O bond lengths ranging from 2.573 (3) to 2.847 (5) Å. The nitrate anions act as bidentate ligands, displaying both terminal and bridging coordination modes. The structure features a robust coordination network supported by hydrogen bonding. These results provide insight into the coord-ination behaviour of Sr<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">II with nitrate and urea ligands, contributing to the understanding of supra-molecular architectures in metal-organic frameworks (MOFs).